Morphology of Residential Environment of Singengu Village in Mandailing Julu, North Sumatra - Cut Nuraini (Journal of Regional and City Planning, 2019)
This study aimed to determine the morphology of the residential environment of Singengu Village in Mandailing Julu between 1880 and 2019. This time frame was taken because primary data that available were refer to that range of years. This research is an interpretive historical research that narratively constructs the morphology of the residential environment in Singengu Village through four sources: archives, documents, evidence from the location, and explanations from interviewees/eyewitnesses. The result showed that the morphological component of Singengu Village's residential environment includes three main aspects, namely: land-use pattern, building layout, and the road network. The roads in Singengu Village's residential environment are quite unique because they were formed after the construction of the residential area and not vice versa. Aspects of the land use and urban design patterns have a typical Mandailing character because they are consistent with the local concept of bincar-bonom.Abstrak. Penelitian ini bertujuan untuk menentukan morfologi lingkungan perumahan di Desa Singengu di Mandailing Julu antara tahun 1880 dan 2019. Kerangka waktu ini diambil karena data primer yang tersedia merujuk pada rentang tahun tersebut. Penelitian ini adalah penelitian sejarah interpretatif yang secara naratif membangun morfologi lingkungan perumahan di Desa Singengu melalui empat sumber: arsip, dokumen, bukti dari lokasi, dan penjelasan dari narasumber/saksi mata. Hasil penelitian menunjukkan bahwa komponen morfologis lingkungan perumahan Desa Singengu meliputi tiga aspek utama, yaitu: pola penggunaan lahan, tata letak bangunan, dan jaringan jalan. Jalan-jalan di lingkungan perumahan Desa Singengu cukup unik karena terbentuk setelah pembangunan daerah perumahan dan bukan sebaliknya. Aspek penggunaan lahan dan pola desain perkotaan memiliki karakter Mandailing yang khas karena konsisten dengan konsep lokal bincar-bonom.Kata kunci. Morfologi, lingkungan perumahan, penggunaan lahan, tata letak bangunan, bincar-bonom.